Article RETRACTED due to manipulation by the authors Differences in Achievement in Physical Education Learning Outcomes for High School Students Based on Parental Occupation: Analysis of Differences in Parental Social Status in Providing Learning Motivation - Riko Septiantoko; Mukhammad Murdiono; Saliman Saliman; Hendra Setyawan; José Vicente García-Jiménez; Francesca Latino; Francesco Tafuri; Nuridin Widya Pranoto; Ari Wibowo Kurniawan; Khoiril Anam; Abdul Aziz Purnomo Shidiq; Muhammad Imam Rahmatullah; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This research aims to determine the achievement of Physical Education (PE) learning outcomes based on parents' work and its relationship to differences in parents' social status in providing learning motivation to students. The sample in this research was high school students in DI Province. Yogyakarta Indonesia. Data analysis used descriptive statistics and inferential factorial one-way ANOVA. One-way anova test results Sig. 0.000 < 0.05 so there is a significant difference in the average of the three PE learning outcomes between students whose parents are civil servants, farmers and entrepreneurs. First Post Hoc follow-up test Sig. 0.000 < 0.05, so that there is a difference in the PE learning achievement of students with their parents' jobs as civil servants and farmers. Post Hoc follow-up test for both Sig. 0.375 > 0.05 so that there is no difference in the PE learning achievement of students with their parents' jobs as civil servants and entrepreneurs. Post Hoc follow-up test for the three Sig. 0.001 < 0.05 so that there is a difference in the PE learning achievement of students whose parents are farmers and entrepreneurs. The conclusion of this research is that there is a significant difference in the average achievement of PE learning outcomes for high school students based on the social status of parents' jobs as civil servants, farmers and entrepreneurs. The social status of parents' work has an influence on the PE learning achievements of high school students in relation to providing learning motivation for students. Working as a civil servant requires a person to have a formal education of at least a bachelor's degree, while for farmer and self-employed jobs it is not required to have a formal bachelor's degree. Parents who work as civil servants and have formal educational experience of at least a bachelor's degree, at least have a tendency to motivate their children to achieve good learning outcomes in compulsory subjects such as PE or other compulsory subjects. However, the farming profession could be stronger and higher in providing learning motivation to their children, with the hope that their children who are still studying at high school level will not become farmers like their parents and can continue at a higher level of formal education.